1992
DOI: 10.1002/mrd.1080310106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxygen toxicity on early development of mouse embryos

Abstract: To examine the effects of oxygen toxicity on embryonic development, mouse pronuclear embryos were cultured under low oxygen conditions with or without superoxide dismutase (SOD), and the blastulation rate was compared with that of embryos cultured under standard conditions. The blastulation rate of mouse pronuclear embryos cultured under standard conditions was only 1.5% (2/131). This rate was increased significantly, to 28.5% (43/151), when the embryos were cultured under low oxygen conditions; and to 31.0% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
75
1
6

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(89 citation statements)
references
References 43 publications
(30 reference statements)
6
75
1
6
Order By: Relevance
“…The presence of SOD has been found to be beneficial during in vitro maturation and fertilization of porcine oocytes (Park et al 1996), and it was also found to have beneficial effects on bovine embryonic development in vitro (Liu and Foote 1995). Moreover, several studies of mouse embryos (Noda et al 1991;Umaoka et al 1992;Chun et al 1994) indicate that the two-cell block occurring in vitro could be alleviated by protection against oxidative stress mediated by SOD action. On the other hand, Luvoni et al (1993) have observed that the addition of SOD from the time of oocyte collection to Day 8 of culture under 5% CO 2 in air improved the cleavage rate of in vitro-inseminated bovine oocytes, although not during further stages of development.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of SOD has been found to be beneficial during in vitro maturation and fertilization of porcine oocytes (Park et al 1996), and it was also found to have beneficial effects on bovine embryonic development in vitro (Liu and Foote 1995). Moreover, several studies of mouse embryos (Noda et al 1991;Umaoka et al 1992;Chun et al 1994) indicate that the two-cell block occurring in vitro could be alleviated by protection against oxidative stress mediated by SOD action. On the other hand, Luvoni et al (1993) have observed that the addition of SOD from the time of oocyte collection to Day 8 of culture under 5% CO 2 in air improved the cleavage rate of in vitro-inseminated bovine oocytes, although not during further stages of development.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies with mouse embryos (Noda et al, 1989Nonogaky et al, 1991;Umaoka et al, 1991Umaoka et al, , 1992Chun et al, 1994) indicate that the two-cell block occurring in vitro could be alleviated by protection against oxidative stress mediated via a potent scavenger of oxygen radicals, superoxide dismutase (SOD). Moreover, Legge and Sellens (1991) reported that when reduced glutathione (GSH) was added to a serum-free medium for the culture of mouse embryos, development to the morula or blastocyst stage was promoted, but neither SOD nor catalase had any effect on the embryonic development.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, an additive effect of low oxygen and SOD on mouse embryo development has been demonstrated (48). These results suggest that mouse 2-cell block is due to damage to the embryos by oxygen radicals.…”
Section: Distribution Of Cuzn-sod In Genital Organsmentioning
confidence: 72%